The tradeoffs in leaning against the wind - François Gourio; Anil K. Kashyap; Jae W. Sim (Federal Reserve Bank of Chicago, 2017)
Credit booms sometimes lead to financial crises which are accompanied with severe and persistent economic slumps. Does this imply that monetary policy should "lean against the wind" and counteract excess credit growth, even at the cost of higher output and inflation volatility? We study this issue quantitatively in a standard small New Keynesian dynamic stochastic general equilibrium model which includes a risk of financial crisis that depends on "excess credit". We compare monetary policy rules that respond to the output gap with rules that respond to excess credit. We find that leaning against the wind may be attractive, depending on several factors, including (1) the severity of financial crises;(2) the sensitivity of crisis probability to excess credit; (3) the volatility of excess credit; (4) the level of risk aversion.
Keywords: E52; E58; G28; 330; Geldpolitik; Geldmengensteuerung; Kreditmarkt; Finanzkrise; Stabilisierungspolitik; Theorie